Tertiary lymphoid structures as local perpetuators of organ-specific immune injury: implication for lupus nephritis - Wang, Meiying; Rajkumar, Snehin; Lai, Yupeng; Liu, Xingjiao; He, Jing; Ishikawa, Tatsuya; Nallapothula, Dhiraj; Singh, Ram Raj (Frontiers in Immunology, 2023)
In response to inflammatory stimuli in conditions such as autoimmune disorders, infections and cancers, immune cells organize in nonlymphoid tissues, which resemble secondary lymphoid organs. Such immune cell clusters are called tertiary lymphoid structures (TLS).Here, we describe the potential role of TLS in the pathogenesis of autoimmune disease, focusing on lupus nephritis, a condition that incurs major morbidity and mortality. In the kidneys of patients and animals with lupus nephritis, the presence of immune cell aggregates with similar cell composition, structure, and gene signature as lymph nodes and of lymphoid tissue-inducer and -organizer cells, along with evidence of communication between stromal and immune cells are indicative of the formation of TLS. TLS formation in kidneys affected by lupus may be instigated by local increases in lymphorganogenic chemokines such as CXCL13, and in molecules associated with leukocyte migration and vascularization. Importantly, the presence of TLS in kidneys is associated with severe tubulointerstitial inflammation, higher disease activity and chronicity indices, and poor response to treatment in patients with lupus nephritis. TLS may contribute to the pathogenesis of lupus nephritis by increasing local IFN-I production, facilitating the recruitment and supporting survival of autoreactive B cells, maintaining local production of systemic autoantibodies such as anti-dsDNA and anti-Sm/RNP autoantibodies, and initiating epitope spreading to local autoantigens. Resolution of TLS, along with improvement in lupus, by treating animals with soluble BAFF receptor, docosahexaenoic acid, complement inhibitor C4BP(β-), S1P1 receptor modulator Cenerimod, dexamethasone, and anti-CXCL13 further emphasizes a role of TLS in the pathogenesis of lupus. However, the mechanisms underlying TLS formation and their roles in the pathogenesis of lupus nephritis are not fully comprehended. Furthermore, the lack of noninvasive methods to visualize/quantify TLS in kidneys is also a major hurdle; however, recent success in visualizing TLS in lupus-prone mice by photon emission computed tomography provides hope for early detection and manipulation of TLS.